COMPARATIVE EFFECTIVENESS OF LECTURE AND MATERIAL-BASED INTERACTIVE METHODS ON SELF-CONCEPT, TEST ANXIETY AND ACHIEVEMENT IN MATHEMATICS IN LAGOS STATE (1995)
This study was carried out with the aim of investigating the effect of three instructional methods and gender on achievement, test anxiety and self-concept in mathematics of NCE year one Business Education Students. The design used was a 3 x 2 pre-test/post-test quasi-experimental design. A sample of 165 first year NCE Business Education Students comprising 71 males and 94 females, with mean age of 22.96 years, was used in this study. The subjects were all full-time students from two colleges of Education in Lagos State who registered for the 1992/93 session. A total of nine hypotheses were tested with respect to the interactive effect of instructional method and gender on each of the three dependent variables. The instructional methods occurred at three levels as follows: Interactive learning with individual use of materials, interactive learning with group use of material and the lecture method. The materials were prepared from the second semester business mathematics course outline. Five instruments were used for data collection. They were: 1. A multiple choice test in mathematics to test prerequisite skills. 2. A multiple choice post achievement test in mathematics covering the course objectives of the second semester business mathematics course. 3. The Inventory of Test Anxiety in Mathematics (ITAM) by Osterhouse,. 4. A mathematics self-concept scale. 5. A learning package. Analysis of covariance was done for each of the three dependent variables. Where significant interaction was found the hypothesis on main effect was not tested. Rather, Scheffe multiple Range Test was used to identify the source of variation. In case of no interaction, Multiple Classification Analysis was used to determine the magnitude and direction of the effect as well as the amount of variation accounted for by each variable. The result showed significant interactive effect of gender and treatment on mathematics achievement. Interactive learning with individual use of materials favoured females while interactive learning with group use of materials favoured males. There was no interactive effect of gender and instructional method on the other two dependent variables. However, with test anxiety as the dependent variable, it was found that instructional method had significant effect, with students exposed to the lecture method having the highest anxiety level when compared with others. The hypothesis on self-concept showed that gender had significant effect, favouring females. Instructional method and gender accounted for a total variance of 24.3% in mathematics test anxiety and 22.8% in self concept in mathematics. Recommendations are made as to how interactive learning could be used to meet students individual needs in the teaching of tertiary mathematics.